2021
DOI: 10.1016/j.dld.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and comorbidity pattern of HCV infected migrants compared to native patients in care in Italy: A real-life evaluation of the PITER cohort

Abstract: Background: Direct-acting antivirals are highly effective for the treatment of hepatitis C virus (HCV) infection, regardless race/ethnicity. We aimed to evaluate demographic, virological and clinical data of HCVinfected migrants vs. natives consecutively enrolled in the PITER cohort. Methods: Migrants were defined by country of birth and nationality that was different from Italy. Mann-Whitney U test, Chi-squared test and multiple logistic regression were used. Results: Of 10,669 enrolled patients, 301 (2.8%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The study was conducted in the pre-DAA era, with treatments ranging from 6 to 12 months based on peg-IFN and ribavirin. Consistent data regarding DAAs were reported from the PITER cohort, which also reported no differences in liver injury between native and migrants [43]. On this regard, Prestileo et al reported no liver cirrhosis among 18 patients evaluated by ultrasound or fibroscan ® .…”
Section: Clinical Features and Outcomessupporting
confidence: 57%
See 1 more Smart Citation
“…The study was conducted in the pre-DAA era, with treatments ranging from 6 to 12 months based on peg-IFN and ribavirin. Consistent data regarding DAAs were reported from the PITER cohort, which also reported no differences in liver injury between native and migrants [43]. On this regard, Prestileo et al reported no liver cirrhosis among 18 patients evaluated by ultrasound or fibroscan ® .…”
Section: Clinical Features and Outcomessupporting
confidence: 57%
“…Unfortunately, the legal status of the subjects was not reported [42]. However, data from the Italian PITER cohort (Italian platform for the study of viral hepatitis therapy) report a higher number of positive females among migrants when compared to natives [43]. Thus, the burden of HCV on female migrants deserves further studies and should better define epidemiology according to Nationality.…”
Section: Epidemiologymentioning
confidence: 99%
“…Regarding HBV infection, the most frequent genotypes in the Italian population are D and A 21 , although other genotypes have been introduced due to immigration, mainly from Africa 22 , 23 . Concerning the HCV genotype, distribution of variants differs between Italian and non-Italian national populations, genotype 4 is much more prevalent among non-Italian residents whereas genotypes 1b and 2 are the most frequent ones among Italian natives 24 .…”
Section: Introductionmentioning
confidence: 99%